Rational-irrational dialectic in the theory of planned behavior in cosmetic use in Malaysia - Muthusamy, Geetha (2019)
The Theory of planned behaviour (TPB) is a model that is based largely on cognition i.e., logical cognition (Ajzen & Fishbein ,1980). As a result, the rational component in TPB predominates in influencing the dependent variable that is intention; meaning that, TPB largely ignores the role of irrational influences in decision making. The study, being explorative, attempts to extend the social-psychological behavioural model i.e. Theory of Planned Behavior (TPB) by including two moderators i.e., Cognitive Bias and Irrational Beliefs to predict female consumers purchase decision towards cosmetic products due to the intense competition identified in cosmetics industries. These two moderators are quite prevalent in the psychological domain. Hence, to the extent that it can incorporate the measurement of irrational variations, this research postulates that TPB can be improved as a model of behavioural intention. To this end, to complement cognitive rationality which is already present in the TPB model, this research will introduce irrational factors to complete the picture. Further, this study evaluates the Purchase Decision Behavior of consumer to test the Intention- Behavior relationship. A self-administered questionnaire was employed to gather data from 380 consumers via purposive sampling and subsequently analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The questionnaire was distributed to female cosmetic users who are 18 years old and older in Klang Valley. Overall, this study proposes thirteen (13) hypotheses. In addition, the proposed moderators, Cognitive Bias tend to strengthen the Behavioral Beliefs and Attitude, Normative Beliefs and Subjective Norms relationship; meanwhile, Irrational Beliefs are found to strengthen the Attitude and Intention, Subjective Norms and Intention relationships. Thus, the findings of this study contribute to the existing theory and practice by using psychological theories beyond its original domain on study through the verification of the framework; and its practical contribution consequently provides useful insights to assist marketers of cosmetic industries to create effective integrated marketing communication strategies (IMC) that incorporate the concurrent influence of both, rational and irrational elements, in the decision making of consumers; with the result that marketers would have a more realistic and pragmat ic model on which to guide their marketing strategies.